Predicates and functions

F1

Write the formula that represents the fact that the predicate P is symmetric.

∀x.∀y. (P x y) ⇒ (P y x)

F2

Write the formula that represents the fact that the predicate P is transitive.

∀x.∀y.∀z. ((P x y) ∧ (P y z)) ⇒ (P x z)

or

∀x.∀y.∀z. (P x y) ⇒ (P y z) ⇒ (P x z)

F3

Write the formula that represents the fact that a function f with one parameter is injective. One can assume the existence of an equality predicate, written x=y.

∀x.∀y. (f x)=(f y) ⇒ x = y

F4

Write the formula that represents the fact that a function f with one parameter is surjective.

∀y.∃x. y=(f x)

Natural Deduction

G1

Prove that (∃x. ∀y. (P x y)) ⇒ (∀y. ∃x. (P x y)).

 
 
 
∃x. ∀y. (P x y)
       
∀y. (P a y)
(P a c)
∃x. (P x c)
∃x. (P x c)
∀y. ∃x. (P x y)
(∃x. ∀y. (P x y)) ⇒ (∀y. ∃x. (P x y))

G2

Prove that (∀y. ∃x. (P x y)) ⇒ (∃x. ∀y. (P x y)).

There is no such a proof.

G3

Prove that (¬(∃x. (P x))) ⇒ (∀x. ¬(P x)).

(P c)
∃x. (P x)
       
 
¬(∃x. (P x))
False
¬(P c)
∀x. ¬(P x)
(¬(∃x. (P x))) ⇒ (∀x. ¬(P x))

G4

Prove that (∀x. ¬(P x)) ⇒ ¬ (∃ x. (P x)).

 
 
 
∃x. (P x)
 
(P c)
       
∀x. ¬(P x)
¬(P c)
False
False
¬(∃x. (P x))
(∀x. ¬(P x)) ⇒ ¬ (∃x. (P x))

G5

Prove that (∃x. ¬(P x)) ⇒ ¬(∀x. (P x)).

 
 
 
∃x. ¬(P x)
∀x. (P x)
(P c)
       
 
¬(P c)
False
False
¬(∀x. (P x))
(∃x. ¬(P x)) ⇒ ¬(∀x. (P x))

G6

Prove in the classical logic that ¬(∀x. (P x)) ⇒ (∃x. ¬(P x)).

¬(P c)
∃x. ¬(P x)
       
 
¬(∃x. ¬(P x))
False
(P c)
∀x. (P x)
       
 
 
 
 
 
¬(∀x. (P x))
False
∃x. ¬(P x)
¬(∀x. (P x)) ⇒ (∃x. ¬(P x))

G7

Prove in the classical logic that ((∀x. (P x)) ⇒ Q) ⇒ ∃x. ((P x) ⇒ Q).

First suppose that ∀x. (P x) is true:

(∀x. (P x))⇒ Q         ∀x. (P x)
Q
(P a) ⇒ Q
∃x. ((P x) ⇒ Q)
((∀x. (P x)) ⇒ Q) ⇒ ∃x. ((P x) ⇒ Q)

Second suppose that ¬(∀x. (P x)) is true, so by G1 we know that ∃x. ¬(P x) is true.

 
 
 
 
 
∃x. ¬(P x)
       
(P c)         ¬(P c)
False
Q
(P c) ⇒ Q
∃x. ((P x) ⇒ Q)
∃x. ((P x) ⇒ Q)
((∀x. (P x)) ⇒ Q) ⇒ ∃x. ((P x) ⇒ Q)

G8

Prove that (∃x. ((P x) ⇒ Q)) ⇒ ((∀x. (P x)) ⇒ Q).

 
 
 
∃x. ((P x)⇒Q)
       
 
(P a)⇒Q
       
∀x. (P x)
(P a)
Q
Q
(∀x. (P x)) ⇒ Q
(∃x. ((P x) ⇒ Q)) ⇒ ((∀x. (P x)) ⇒ Q)

G9

Prove that ((∃x. (P x)) ⇒ Q) ⇒ ∀x. ((P x) ⇒ Q).

 
 
(∃x. (P x))⇒Q
       
(P c)
∃x. (P x)
Q
(P c)⇒Q
∀x. ((P x) ⇒ Q)
((∃x. (P x)) ⇒ Q) ⇒ ∀x. ((P x) ⇒ Q)

G10

Prove that (∀x. ((P x) ⇒ Q)) ⇒ ((∃x. (P x)) ⇒ Q).

 
 
 
∃x. (P x)
       
       
∀x. ((P x) ⇒ Q)
(P c) ⇒ Q
 
(P c)
Q
Q
(∃x. (P x)) ⇒ Q
(∀x. ((P x) ⇒ Q)) ⇒ ((∃x. (P x)) ⇒ Q)

G11

Prove that (Q ⇒ (∀x. (P x))) ⇒ ∀x. (Q ⇒ (P x)) .

Q⇒ (∀x. ((P x))         Q
∀x. (P x)
(P c)
Q ⇒ (P c)
∀x. (Q ⇒ (P x))
(Q ⇒ (∀x. (P x))) ⇒ ∀x. (Q ⇒ (P x))

G12

Prove that (∀x. (Q ⇒ (P x))) ⇒ (Q ⇒ (∀x. (P x))).

∀x. (Q ⇒ (P x))
Q ⇒ (P c)
       
 
Q
(P c)
∀x. (P x)
Q ⇒ (∀x. (P x))
(∀x. (Q ⇒ (P x))) ⇒ (Q ⇒ (∀x. (P x)))

G13

Prove in classical logic that (Q ⇒ (∃x. (P x))) ⇒ (∃x. (Q ⇒ (P x))).

Suppose that the proposition Q is true:

 
Q ⇒ (∃x. (P x))         Q
∃x.(P x)
       
(P c)
Q ⇒ (P c)
∃x. (Q ⇒ (P x))
∃x. (Q ⇒ (P x))
(Q ⇒ (∃x. (P x))) ⇒ (∃x. (Q ⇒ (P x)))

Suppose that the proposition ¬Q is true:

Q         ¬Q
False
(P a)
Q ⇒ (P a)
∃x. (Q ⇒ (P x))
(Q ⇒ (∃x. (P x))) ⇒ (∃x. (Q ⇒ (P x)))

G14

Prove that (∃x. Q ⇒ (P x)) ⇒ (Q ⇒ (∃x. (P x))).

 
 
∃x. (Q ⇒ (P x))
       
Q⇒ (P c)         Q
(P c)
∃x. (P x)
∃x. (P x)
Q ⇒ (∃x. (P x))
(∃x. Q ⇒ (P x)) ⇒ (Q ⇒ (∃x. (P x)))

G15

Prove that ((∀x. (P x)) ∨ Q) ⇒ (∀x. (P x) ∨ Q).

 
 
 
(∀x. (P x))∨ Q
       
∀x. (P x)
(P c)
(P c) ∨ Q
∀x. ((P x) ∨ Q)
       
 
Q
(P c) ∨ Q
∀x. ((P x) ∨ Q)
(∀x. ((P x) ∨ Q)
((∀x. (P x)) ∨ Q) ⇒ (∀x. ((P x) ∨ Q))

G16

Prove in classical logic that (∀x. ((P x) ∨ Q)) ⇒ ((∀x. (P x)) ∨ Q.

Suppose that the proposition Q is true:

Q
(∀x. (P x)) ∨ Q
(∀x. ((P x) ∨ Q)) ⇒ ((∀x. (P x)) ∨ Q)

Suppose that the proposition ¬Q is true:

 
 
(∀x. (P x))∨ Q
       
 
∀x. (P x)
(∀x. (P x))∨ Q
       
Q        ¬Q
False
(∀x. ((P x)) ∨ Q
(∀x. (P x)) ∨ Q
(∀x. ((P x) ∨ Q)) ⇒ ((∀x. (P x)) ∨ Q)

G17

Prove that ((∃x. (P x)) ∨ Q) ⇒ ∃x. ((P x) ∨ Q).

 
 
 
(∃x. (P x))∨ Q
       
 
 
(∃x. (P x))
       
(P c)
(P c) ∨ Q
∃x. ((P x) ∨ Q)
∃x. ((P x) ∨ Q)
       
 
Q
(P a) ∨ Q
∃x. ((P x) ∨ Q)
(∃x. ((P x) ∨ Q)
((∃x. (P x)) ∨ Q) ⇒ (∃x. ((P x) ∨ Q))

G18

Prove that (∃x. ((P x) ∨ Q)) ⇒ (∃x. (P x)) ∨ Q.

 
 
 
∃x. ((P x) ∨ Q))
       
 
 
(P c) ∨ Q
       
(P c)
∃x. (P x)
(∃x. (P x)) ∨ Q
       
 
Q
(∃x. (P x)) ∨ Q
(∃x. (P x)) ∨ Q
(∃x. (P x)) ∨ Q
(∃x. ((P x) ∨ Q)) ⇒ (∃x. (P x)) ∨ Q

G19*

Prove that (P a) ⇒ ((∀x. ((P x) ⇒ (Q x))) ⇒ (Q a)).

∀x. ((P x) ⇒ (Q x))
(P a) ⇒ (Q a)
       
 
(P a)
(Q a)
(∀x. ((P x) ⇒ (Q x))) ⇒ (Q a)
(P a) ⇒ ((∀x. ((P x) ⇒ (Q x))) ⇒ (Q a))

G20*

Prove that (∃x. ((P x) ⇒ (Q x))) ⇒ ((∀x. (P x)) ⇒ (∃x. (Q x))).

 
 
 
∃x. ((P x) ⇒ (Q x))
       
 
∃x. ((P x) ⇒ (Q x))
       
∀x. (P x)
(P c)
(Q c)
∃x. (Q x)
∃x. (Q x)
(∀x. (P x)) ⇒ (∃x. (Q x))
(∃x. ((P x) ⇒ (Q x))) ⇒ ((∀x. (P x)) ⇒ (∃x. (Q x)))

*G21

Prove that (∀x. (P x) ⇒ (Q x)) ⇒ ((∃x. (P x)) ⇒ (∃x. (Q x))) .

 
 
 
∃x. (P x)
       
∀x. ((P x) ⇒ (Q x))
(P c) ⇒ (Q c)
       
 
(P c)
(Q c)
∃x. (Q x)
∃x. (Q x)
(∃x. (P x)) ⇒ (∃x. (Q x))
(∀x. (P x) ⇒ (Q x)) ⇒ ((∃x. (P x)) ⇒ (∃x. (Q x)))

*G22

Prove that (∃x. ((P x) ∧ (Q x))) ⇒ (∃x. ((Q x) ∧ (P x))).

 
 
 
∃x. ((P x) ∧ (Q x))
       
(P c) ∧ (Q c)
(Q c)
       
(P c) ∧ (Q c)
(P c)
(Q c) ∧ (P c)
∃x. ((Q x) ∧ (P x))
∃x. ((Q x) ∧ (P x))
(∃x. ((P x) ∧ (Q x))) ⇒ (∃x. ((Q x) ∧ (P x)))


Monica Nesi